The Association of Alanine Aminotransferase Levels With Myocardial Perfusion Imaging and Cardiovascular Morbidity. (25th January 2022) - Yardeni, David; Toledano, Ronen; Novack, Victor; Shalev, Aryeh; Wolak, Arik; Rotman, Yaron; Etzion, Ohad
Introduction: Studies suggest that non-alcoholic fatty liver disease (NAFLD) is associated with an independent risk of cardiovascular disease (CVD). We utilized a large cohort of patients undergoing myocardial perfusion imaging (MPI) with single photon emission computed tomography (SPECT) to determine the association between alanine aminotransferase (ALT) as a surrogate marker for presumed NAFLD, and the presence of myocardial ischemia and mortality. Methods: We retrospectively assessed SPECT-MPI results and medical records of individuals evaluated between 1997 and 2008. We excluded patients with known non-NAFLD liver diseases, ALT values <17 or >340 U/L and absent liver tests. Elevated ALT cases were classified as presumed NAFLD. The primary endpoint was abnormal SPECT-MPI. Secondary endpoints included cardiac death, acute myocardial infarction and all-cause mortality. Results: Of 26, 034 patients who underwent SPECT-MPI, 11, 324 met inclusion criteria. 1635 (14.4%) patients had elevated ALT. SPECT-MPI results did not differ significantly between subjects with elevated ALT and controls. Elevated ALT was associated with increased risk for the composite endpoint of cardiac death or acute myocardial infarction at 5-year follow-up (hazard ratio [HR] 1.3, 95% confidence interval [CI] 1.01-1.67) and in all-cause mortality (HR 1.27, CI 1.02-1.58) but only in patients with normal SPECT-MPI. Conclusions: The long-term mortality of patients with abnormal SPECT-MPI is not modulated by ALT, likely reflecting an already high risk and established CVD. However, patients with normal SPECT-MPI are at increased risk for a future cardiac event if they have an elevated ALT level, suggesting an important role for NAFLD in earlier stages of CVD.